IMPROVING STUDENTS' ENGLISH VOCABULARY THROUGH THE MEDIA ANIMATION FILM 'JACK AND THE GIANT BEAN TREE' - Endah Sulistianingwarni; Suryadi Suryadi (IKIP Siliwangi, 2023)
This study aims to determine the effect of the animated film media